Irreversibility analysis of falling film absorption over a cooled horizontal tube. (September 2015) - Giannetti, Niccolò; Rocchetti, Andrea; Saito, Kiyoshi; Yamaguchi, Seiichi
Highlights: Local entropy generation distribution within an absorptive film. Parametric analysis of the entropy generation rates related to different irreversibility sources. Identification of the least irreversible solution mass-flow rate for the absorber. Importance of working at reduced mass flow rates with a thin uniform film. Abstract: Based on a numerical study of the water vapour absorption process in LiBr–H2 O solution, for a laminar, gravity driven, viscous, incompressible liquid film, flowing over a horizontal cooled tube, irreversibilities related to fluid friction, heat transfer, mass transfer and their coupling effects have been locally and globally examined. The hydrodynamic description is based on Nusselt boundary layer assumptions. The tangential and normal velocity components, respectively obtained from momentum and continuity equations, have been used for the numerical solution of mass and energy transport equations in the two-dimensional domain defined by the film thickness and the position along the tube surface. Local entropy generation calculation can be performed referring to the calculated velocity, temperature and concentration fields. Results have been explored in different operative conditions, in order to examine comprehensively the impact of the various irreversibility sources and to identify the least irreversible solution mass flow-rate for the absorber. As a parallel, a refined understanding of the absorption process can be obtained. Considering absorption at the film interface and cooling effect at the tube wall, the analysis thermodynamically characterises the absorption process which occurs inside actual falling film heat exchangers and establishes a criterion for their thermodynamic optimisation. Results suggest the importance to operate at reduced mass flow rates with a thin uniform film. Meanwhile, tension-active additives are required to realise this condition.